2013
DOI: 10.4104/pcrj.2013.00052
|View full text |Cite
|
Sign up to set email alerts
|

Global strategies for reducing the burden from asthma

Abstract: Asthma is one of the most important chronic diseases in childhood. For several decades, a steady increase in prevalence has been observed worldwide. In the structural collaboration between the Centre for Population Health Services in Edinburgh and the Research Institute CAPHRI of Maastricht we investigated the possibilities for primary prevention of asthma in childhood. We found that a multifaceted approach might be effective in delaying or preventing asthma, whereas a mono-intervention does not seem to have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
(41 reference statements)
0
15
0
2
Order By: Relevance
“…This diagnostic delay could be due to the communication difficulties between patients and physicians; indeed, most patients do not report their bronchial symptoms to the general practitioner remaining undiagnosed. On the other hand, patients with respiratory problems and reduced lung function are not always recognized as such, may be due to a lack of guidelines awareness or implementation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This diagnostic delay could be due to the communication difficulties between patients and physicians; indeed, most patients do not report their bronchial symptoms to the general practitioner remaining undiagnosed. On the other hand, patients with respiratory problems and reduced lung function are not always recognized as such, may be due to a lack of guidelines awareness or implementation …”
Section: Discussionmentioning
confidence: 99%
“…Italian data showed the need for reducing the diagnostic delay, through an early detection of asthma and a subsequent early treatment, in order to improve the long‐term prognosis of these patients, probably preventing the development of long‐term modifications, such as remodeling, with a subsequent further impairment in pulmonary function …”
Section: Discussionmentioning
confidence: 99%
“…The global prevalence of asthma in children has risen significantly over the recent decades [4], [5]. The exact cause of this increase is not known, but associations with increasing urbanization have been reported [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the prevalence of asthma is increasing considerably over the past 20 years [2]. Asthma is a chronic pulmonary disease featured by airway inflammation, airway hyperreactivity (AHR) and airway remodeling [3,4].…”
Section: Introductionmentioning
confidence: 99%